Design de Visualizações Narrativas Interativas - Queiroz Santos, Caroline; Selbach Silveira, Milene (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2018.4173, 2018)
Narrative visualization is an emerging data visualization field and has been used for the purpose of communicating information efficiently and intuitively as well as providing greater engagement in data exploration. In this mini-course, we will present and discuss fundamental concepts for interactive narrative visualizations design, and explore these concepts - in theory, and practice - by means of a model that aims to enable reflection on decisions to be taken in narrative visualization’s design.